Examining police officers’ preparedness and attitude in conducting investigative interviews in the Philippines - Tañola, Eroll; Marquez, Jan Carlo; Dauplo , Zyra Jane; Daang, Sherilyn; Nacionales, Joseph; Claridad, Norberto (Journal of Language and Pragmatics Studies, 2023)
The field of police examinations has made great strides shifting towards a more ethical and basic aspiration of amplifying the quality and volume of data from suspects, rather than the narrow focus on carrying a concession of guilt (Milne & Bull 1999). In recent studies, analysis of the inquiry-based practices of interviews with suspects and accused persons showed that appropriate practices are not being used often. (Snook et al, 2012). It revealed that most of the officers used counter- productive and risky questions that limited narrative responses from the youth offenders (Del Rosario & Ballesteros-Lintao,  2018). Using qualitative research through interpretative phenomenological analysis (IPA), this study aims to examine the attitudes employed and the preparations done before conducting an investigative interview. Nine transcripts of audio-recorded interviews from various investigative officers of Tacloban City police officers were analyzed using thematic analysis. The results yielded reveals that there are positive relations between the police officers’ attitudes and presentation in conducting investigative interviews. Participants who can build rapport and are equipped with necessary tools and information can generate reliable and more extensive information.